Folk Devotion in the Waterscape of the Pasig River: The 1653 and 1748 Fluvial Processions of the Nuestra Señora de la Paz y Buen Viaje - Nito, Mary Josefti C. (BANWAAN: The Philippine Journal of Folklore, 2022)
The Nuestra Señora de la Paz y Buen Viaje or Our Lady of Antipolo is one of the most prolific Marian sites or devotions in the Philippines. The image of Our Lady of Antipolo also served as the patroness of some galleon ships during the 17th and 18th century. The return of the image to its shrine in Antipolo would be occasions for a fluvial procession along the Pasig River. This paper analyzes the 1653 and 1748 fluvial processions of the Nuestra Señora de la Paz y Buen Viaje along the Pasig River as documented by Pedro Murillo Velarde S.J., which were reprinted in 1887 as the Historia de la Nuestra Señora de la Paz y Buen Viaje. The detailed descriptions from this account captures the waterscape of the Pasig River during the procession, which Velarde compares to a theater because of the great number of people in attendance. The account also details the performance of folk devotion particularly from the Tagalog towns participating in the procession. By focusing on the Pasig River, this study brings to the fore the value of the river as a cultural-religious space unifying the Tagalog towns that complete its waterscape. Lastly, the conclusions of this study highlight the communal experience of the procession and the role of popular devotions in the articulation of folk culture and identity especially during early modern colonial Philippines. Keywords: Our Lady of Antipolo, Pasig river, fluvial processions, folk devotion, waterscape